Caries-Preventive Effect and Retention of Glass-Ionomer and Resin-Based Sealants: A Randomized Clinical Comparative Evaluation. (20th June 2022) - Uzel, Ilhan; Gurlek, Ceren; Kuter, Berna; Ertugrul, Fahinur; Eden, Ece
Abstract : Background . Deep fissures are highly unprotected from the development of caries. Resin-based materials and glass-ionomer cements for sealing fissures are useful in caries control through physical barrier formation, which prohibits metabolic exchange between fissure microorganisms. Retention is one of the most critical properties of fissure sealants. This in vivo study is aimed at comparing and evaluating the clinical efficacy of resin and glass ionomer-based fissure sealants on first permanent molars with follow-ups at 6-, 12-, and 18-month intervals. Methods . A randomized split-mouth design clinical study was conducted after obtaining the ethical committee approval. A total of 50 patients, aged between 7 and 12 years, were randomized and enrolled in the study to perform a total of 200 sealant placements on all four caries-free and hypoplasia-free first permanent molars having deep fissures, which are susceptible to caries, were included in this study. The four permanent molars were divided into the following four groups: group A (control), B (Grandioseal, Voco, Germany), C (Smartseal & Loc, Detax Gmbh & Co, Germany), and D (Fuji triage capsule, GC, Belgium). The sealed molars were clinically evaluated at intervals of 6, 12, and 18 months to assess sealant retention, surface roughness, marginal coloration, and caries status through visual evaluation of the sealant by two evaluators. Results . Concerning retention, there were statistically significant differences between the sealants in terms of the survival of partial and fully retained sealants as well as in the survival of caries-free teeth. Two resin-based (Smartseal & Loc) and glass-ionomer cement (Fuji triage) sealants showed significantly similar performances in permanent molars for up to 18 months. In terms of retention, one of the resin-based (Grandioseal) sealants performed better as compared to the others and showed better caries prevention in deep fissures. Conclusion . It is concluded that both the sealants had comparable retention and caries-preventive effects in 7 to 12-year-old children and can be considered as suitable sealants for a period of at least 18 months in moderate caries risk patients.